REPTILES - Indraneil, Das; Izneil, Nashriq; Taha, Wahab (UNIMAS Publisher, Sarawak Forestry Corporation and Natural History Publications (Borneo) Sdn. Bhd., 2025)
The chapter enumerates the reptile fauna of Niah National Park, Miri, Sarawak.